Plano de gerenciamento de riscos: um estudo sobre o setor de obras da ufersa - Bezerra, Diego Henrique Bandeira (Universidade Federal Rural do Semi-Árido, 2019)
The theme risk, in several areas, is becoming recurrent, being highlighted at the media, mainly when there are tragedy cases, accidents or loss of financial resources. These facts generate questions concerning the accomplishment of preventive actions to minimizing its impacts. In the corporative environment, measures should be also adopted to guarantee the fulfilling of the institutional objectives. In this sense, the Normative Instruction MP/CGU No. 01/2016 has brought some innovations to the administrative environment of the public institutions of Federal Executive Power, being the use of risk management the main innovation in its daily processes. However, there is a problematic of how to insert these changes in the administrative environment. In this sense, this research aims to propose a model of management risk plan in the procedures of construction planning at UFERSA. The research has used the qualitative method, the strategy of case study and documental, observational and interviewing research techniques. The interviews were not standardized and not directed and it was applied the model of implementation of risk management proposed by the COSO ERM. By analyzing the data, it has been verified that the contracts of constructions in the institution in the period from 2013 to 2018 have suffered multiples alterations of value without scheduled actions to mitigate these sorts of occurrence, as it was also verified that the Policy of Risk Management of UFERSA does not assist completely the established in IN 01/2016. In view of that, it was accomplished a proposal of intervention, with the proposition of alterations in the process of construction planning of the institution from the methodology of COSO ERM. This work will assist in the implementation process of risk management of UFERSA and will contribute to the improvement of the construction planning process of the institution.
Keywords: Gestão; Riscos; Procedimentos; Planejamento; Obras; Management; Risks; Procedures; Planning; Construction; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA